Ovarian Cancer - Updates in Tumour Biology and Therapeutics [Working Title] 2021
DOI: 10.5772/intechopen.98289
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Tumour Biology: Genesis

Abstract: Ovarian cancer (OC) is the fifth leading cause of cancer deaths among women, thus early diagnosis is of paramount importance to survival. A clear OC etiopathogenesis is not yet fully understood. Large histopathological variability predicts more initial tissue for carcinogenesis. Many connections of biologically different tissue as locus minoris resistentiae for carcinogenesis have been confirmed. Expansion of knowledge about OC etiopathogenesis may help to construct an algorithm for early diagnosis. Ovarian su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results showed that the selectivity indices of carboplatin and plasma-activated medium (PAM) for A2780 CP and SKOV-3 were significantly higher than those of traditional chemotherapeutic drugs. Particularly, PAM with 10% FBS exhibited the highest selectivity towards OC cells among all plasma treatment methods, surpassing the selectivity of various plasma therapies and conventional chemotherapeutic drugs [ 163 ].…”
Section: New Approaches To Overcome Drmentioning
confidence: 99%
“…The results showed that the selectivity indices of carboplatin and plasma-activated medium (PAM) for A2780 CP and SKOV-3 were significantly higher than those of traditional chemotherapeutic drugs. Particularly, PAM with 10% FBS exhibited the highest selectivity towards OC cells among all plasma treatment methods, surpassing the selectivity of various plasma therapies and conventional chemotherapeutic drugs [ 163 ].…”
Section: New Approaches To Overcome Drmentioning
confidence: 99%